(untitled) (ResearchJet Journal of Analysis and Inventions, 2020)
The article reveals the importance of economic diagnostics in the study of higher education. The role of economic diagnostics in ensuring the effectiveness of the higher education institution and the importance of diagnostic models are highlighted. Scientific proposals and practical recommendations for the diagnosis of the economic and financial condition of the higher education institution or trends in it are given.